1992
DOI: 10.1073/pnas.89.18.8507
|View full text |Cite
|
Sign up to set email alerts
|

Existence of two pathways for the endocytosis of epidermal growth factor by rat liver: phenylarsine oxide-sensitive and -insensitive pathways.

Abstract: The effect of phenylarsine oxide (PAO) on the internalization rate of epidermal growth factor (EGF) was investigated using perfused rat liver and isolated rat hepatocytes. In perfused liver, a tracer concentration of 125I-EGF alone or with excess unlabeled EGF (20 nM) was perfused and the internalization rate constants (knJ) were measured. In the absence of PAO, kint values did not differ significandly for either dose condition. However, with the addition of PAO to the perfusate, the kint value dropped to 4% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…4 and 5. The rate of internalization of pullulan into cultured rat liver parenchymal cells was estimated by the method of Kato et al 9) From the initial slope of plots shown in Fig. 2, the internalization rate of pullulan (k int ) was estimated at 0.30Ϯ0.13 min…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 and 5. The rate of internalization of pullulan into cultured rat liver parenchymal cells was estimated by the method of Kato et al 9) From the initial slope of plots shown in Fig. 2, the internalization rate of pullulan (k int ) was estimated at 0.30Ϯ0.13 min…”
Section: Resultsmentioning
confidence: 99%
“…The amount of protein was determined by the method of Lowry et al 8) Data Analysis Internalization data were analyzed by Eq. 1 according to the method described by Kato et al 9) ( 1) where I t is the amount of internalization at time t, k int is the rate constant of initial internalization, and L s is the amount bound to the cell surface. The value of k int was estimated from the initial slope of…”
Section: Methodsmentioning
confidence: 99%
“…7), a feature that probably accounts for previously reported complex effects of PAO on signal transduction pathway intermediates and enzymatic activities. For example, regulated fluctuations in intracellular calcium concentration and tyrosine phosphorylation of a number of different phosphoproteins have been reported to be either inhibited or enhanced by PAO, the outcome depending on the signaling pathway or protein investigated and the timing and concentration of PAO application [38,[44][45][46][47][48][49][50][51][52][53]. Thus, it seems unlikely that LFA-1 adhesion-regulatory processes are an exclusive target of PAO, but rather represent one of a number of PAO-sensitive physiological processes.…”
Section: Lfa-1 Conformation and Cytoskeleton Interactionsmentioning
confidence: 99%
“…It is known that endocytosis is involved in the internalization mediated by antigens and receptors in various biologically active proteins and therapeutic antibodies (Pulczynski et al, 1994;Kato et al, 1996Kato et al, , 1997Lammerts van Bueren et al, 2006). Indeed, internalization of 125 I-AHM by KPMM2 cells in the presence of PAO (Finbloom, 1988;Kato et al, 1992), which is an endocytosis inhibitor, was significantly decreased (i.e., 1/21 that in the absence of PAO). Consistent with our recent results (Masuyama et al, 2009), it is evident that at least some 125 I-AHM was internalized by the endocytosis mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition experiment was conducted in a manner similar to that described above except for the addition of 0.5 mM PAO to the medium, which is known to inhibit the endocytosis of protein (Finbloom, 1988;Kato et al, 1992).…”
Section: ϭ Dose/aucmentioning
confidence: 99%